2016
DOI: 10.1590/1981-6723.3815
|View full text |Cite
|
Sign up to set email alerts
|

Conservation of minimally processed apples using edible coatings made of turnip extract and xanthan gum

Abstract: Summary The objective of this study was to evaluate the potential of turnip extract and xanthan gum in the conservation of minimally processed apples. The apples were washed, sanitized with sodium hypochlorite (200 ppm) for 15 minutes, peeled, and cut into eight pieces prior to being subjected to one of the following treatments in aqueous solution: A – water (control); B – turnip extract; C – turnip extract and CaCl2; D – xanthan gum, CaCl2 and glycerol; E – turnip extract, xanthan gum, CaCl2, and glycerol. Su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 17 publications
1
3
0
2
Order By: Relevance
“…Hernández-Muñoz et al (2008) observed values between 14.2% and 19.6% of mass loss with chitosan coating, stored at 10°C for 7 days. Thus, the mass loss results obtained in this study indicate that the treatments were viable (Borges et al, 2013). Silva et al (2011), working with yellow passion fruit residue biofilms applied to apples, found that the treatments did not prevent mass loss but showed lower values than the control.…”
Section: Physicochemical Analyzessupporting
confidence: 45%
See 1 more Smart Citation
“…Hernández-Muñoz et al (2008) observed values between 14.2% and 19.6% of mass loss with chitosan coating, stored at 10°C for 7 days. Thus, the mass loss results obtained in this study indicate that the treatments were viable (Borges et al, 2013). Silva et al (2011), working with yellow passion fruit residue biofilms applied to apples, found that the treatments did not prevent mass loss but showed lower values than the control.…”
Section: Physicochemical Analyzessupporting
confidence: 45%
“…Another important parameter is the loss of water in the fruits during storage since dehydration causes an increase in the concentration of soluble solids and TA, interfering with the increase in values during storage (Borges et al, 2013).…”
Section: Physicochemical Analyzesmentioning
confidence: 99%
“…Color was analyzed using a Minolta CR-400 colorimeter. The a*, b*, and L* values were used to obtain the browning index (BI) according to Borges et al [ 32 ], Equation (1): where three slices of apple were used for the color test, with six readings per analysis (two readings per slice) every five days during the storage period.…”
Section: Methodsmentioning
confidence: 99%
“…Color was analyzed using a Minolta CR-400 colorimeter. The a*, b*, and L* values were used to obtain the browning index (BI) according to Borges et al [32], Equation ( 1…”
Section: Assay Of Color (Brown Index Bi)mentioning
confidence: 99%
“…Devido a essa elevada perecibilidade, o mamão, mesmo in natura apresenta curta vida de prateleira e quando exposto ao processamento mínimo, como descascamento e corte, pode ter essa perecibilidade acentuada (MARTINS, 2012). Considerando esta característica, o desenvolvimento de novas tecnologias que visam prolongar a conservação desses alimentos tem sido cada vez mais estudadas (BARRETO et al, 2021;BORGES et al, 2016;NEUWALD et al, 2021;TOMAZ et al, 2021).…”
Section: Introductionunclassified